UNRAVELING THE WOUND MANAGEMENT POTENTIALVRANYA DRAVYAS OF BHAVAPRAKASA NIGHANTU - A REVIEW - Kumar, Aswathy P.; Thomson, Robin J.; Sooraj, S. (International Research Journal of Ayurveda & Yoga, 2025)
Wound management, closely associated with the art of surgery, has been described in ayurveda, offering a broad scope for research that can significantly enhance modern wound care practices. Modern research has increasingly validated the therapeutic potential of herbs outlined in traditional Ayurvedic texts. The Bhavaprakasa Nighantu is a lexicon that catalogs an extensive array of medicinal plants and their applications. Numerous Vranya Dravyas identified in the Bhavaprakasa Nighantu have been found to possess antimicrobial, anti-inflammatory, and regenerative properties, offering a sustainable alternative to synthetic drugs in wound care. It alleviates pain, restores function, and improves quality of life while also saving costs on extensive treatments. By combining modern and traditional practices, it promotes natural healing and supports overall well-being This review delves into the wound management potential of these Vranya Dravyas, aiming to bridge the gap between traditional wisdom and contemporary medicine.